DIAGNOSTIC DILEMMA OF BIOTINIDASE DEFICIENCY: CASE OF A CHILD FROM PAKISTAN - Shoaib, Maria; Faraz, Ahmad; Ahmed, Syed Ahsanuddin; Jamil, Marium; Aijaz, Zobia (Journal of Ayub Medical College Abbottabad, 2016)
Biotinidase deficiency is an autosomal recessive in born error of metabolism which is characterized by the lack of cleavage of biotin. This disease has been reported very rarely with the incidence found to be 1 per 60,089 and 1 per 112,271 of live births, respectively. This condition has profound effects on the neurological system, various neurocutaneous manifestations and metabolic derangements. We report a case of 3-year-old male child who presented in ER with severe respiratory distress for 1 day in a tertiary care set up. He had been referred from multiple peripheral centres. His associated complaints included severe rash, restlessness and progressive mental deterioration for 2 years. He was managed on symptomatically initially, later a diagnosis of Biotinidase deficiency was made, he responded well on supplemental biotin. Our intention to document this case was for sake of its uniqueness with very common symptoms, varied presentation and rarity of the disease which makes it a diagnostic dilemma. Keywords: Biotin, Biotinidase deficiency; Metabolic disorder; Diagnostic dilemma